RANCANGAN MEKANIK TRANSMISI DETEKTOR DAN SUMBER PEMINDAI GAMMA - Sanda Sanda (BATAN, 2013)
DESIGN OF TRANSMISSION MECHANICS OF DETECTOR AND SOURCE OF GAMMA SCANNING. Mechanicl transmission system of both detector and source of gamma scanning is equipment for scanning of a column production for chemical and or combustion process to monitor if any nternal component inside the column found defective or any trouble inside the column. To have precision result of the scanning, it is required to have a mechanical transmission system that will not be affected by any vibration coming from both translation movement moving devices and environment wind. Moreover the placement between the detector and the source must be in line coordinate system. This transmission system must be easily used and fit for the available column process on site. To support the requirements, a design has been proposed by placing the source case and the detector used at the gantry arm having a slit for moving direction along the gantry arm. The arm has 2.000 mm in diameter with the possibility to move 1.500 mm up and down. The diameter of the column to be scanned is 1.000 mm, and the design of this mechanical transmission is to be portable so that it can be easily fit to any column process.